The Effects of Breathing Exercise Toward IgG, Beta Endorphin and Blood Glucose Secretion - Siswantoyo, -; Aman, M.S. (Lyceum of the Philippines University, 2014)
This study aimed to demonstrate the influence of breathing exercise to ward IgG, Beta Endorphin and Blood Glucose Secretion In The Elderly. This is experimental research with the pretest–posttest design. The sample used the elderly 10 men aged 35-45 years. The unit of analysis in this study was blood taken from cubity vein, checking the blood glucose levels used glucometer, beta-endorphin and IgG used ELISA method. Data analysis statistics using the SPSS for windows, was conducted the t-tests. The results showed that based on the statistical analysis, IgG significantly (p:0.013). The mean increase in IgG was 33.266 ng/mL, beta-endorphin significantly (p:0.000). The mean increase in endorphin was 3.922 ng/mL, and the decrease of blood glucose showed significant (p:0.000). The mean decrease in blood glucose levels was 28.9 mg/100ml. Blood glucose levels showed a decline after the breathing exercise. Conclusion, It can be concluded that regular, targeted and programmed breathing exercise seven week can increased the secretion of IgG and beta endorphins, as well as decreasing blood glucose levels. Breathing exercise are alternative sports to improve immunity.